2021
DOI: 10.1007/s12325-021-01758-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Congenital Low-Flow Vascular Malformation Treated with Low Dose Sirolimus

Abstract: Introduction Patients with congenital vascular malformations often suffer from an impaired quality of life (QoL) because of pain and functional disabilities. Previous studies have shown that the mTOR inhibitor sirolimus can reduce complaints and improve QoL in some patients. High target levels of sirolimus of 10–15 ng/ml were well tolerated; however, in a relative high percentage of patients sirolimus caused serious adverse events (AEs). Methods A case series of 12 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
4
17
0
Order By: Relevance
“…It has previously been suggested, based on animal studies with mouse models, that low doses of rapamycin (1–5 ng/mL) would be optimal to block intracellular angiogenesis pathways 17 . Our good clinical results support this theory, and in previous publications on low‐flow vascular malformations, similar results have been reported with sirolimus levels lower than those considered the gold standard 18,19 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It has previously been suggested, based on animal studies with mouse models, that low doses of rapamycin (1–5 ng/mL) would be optimal to block intracellular angiogenesis pathways 17 . Our good clinical results support this theory, and in previous publications on low‐flow vascular malformations, similar results have been reported with sirolimus levels lower than those considered the gold standard 18,19 …”
Section: Discussionsupporting
confidence: 86%
“…17 Our good clinical results support this theory, and in previous publications on low-flow vascular malformations, similar results have been reported with sirolimus levels lower than those considered the gold standard. 18,19 Pneumocystis carinii pneumonia (PCP) is a potentially serious AE in patients treated with sirolimus, but no cases were seen in our study, which was possibly due to all patients receiving prophylaxis. However, other authors have published similar data without prophylaxis and only two cases of PCP have been reported in patients receiving sirolimus for a vascular malformation.…”
Section: Discussionmentioning
confidence: 57%
“…In a phase II clinical trial, Adams et al [5] demonstrated the effectiveness of sirolimus in treating pediatric patients with complicated vascular anomalies without apparent BM toxicity. A more recent report by Harbers et al [19] suggested that low-dose sirolimus successfully cured therapy-resistant patients with congenital vascular malformation, although adverse events such as menstrual cycle disturbances were observed in young adult patients. In addition, Sirolimus does have side effects, including immune suppression, hyperlipidemia, and oral ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…This is also seen in our case series of patients with low flow vascular malformations showing that low-dose sirolimus led to less (serious) AEs compared to intermediate-high dose sirolimus. 28 In some case series of KHE patients described in the literature, a dose of 0.8 mg/m 2 twice daily was prescribed, based on standard dosing for off label treatment of vascular anomalies (such as vascular malformation). This dose regimen led to supratherapeutic levels of >30 ng/mL in patients with KHE, which in turn led to serious AEs or even were fatal.…”
Section: Introductionmentioning
confidence: 99%
“…This is also seen in our case series of patients with low flow vascular malformations showing that low‐dose sirolimus led to less (serious) AEs compared to intermediate‐high dose sirolimus. 28 …”
Section: Introductionmentioning
confidence: 99%